2018
DOI: 10.1038/s41467-018-04797-2
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale genetic analysis reveals mammalian mtDNA heteroplasmy dynamics and variance increase through lifetimes and generations

Abstract: Vital mitochondrial DNA (mtDNA) populations exist in cells and may consist of heteroplasmic mixtures of mtDNA types. The evolution of these heteroplasmic populations through development, ageing, and generations is central to genetic diseases, but is poorly understood in mammals. Here we dissect these population dynamics using a dataset of unprecedented size and temporal span, comprising 1947 single-cell oocyte and 899 somatic measurements of heteroplasmy change throughout lifetimes and generations in two genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
70
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 41 publications
(105 reference statements)
11
70
1
Order By: Relevance
“…From stochastic simulations we observed that, for sufficiently short times, heteroplasmy variance increases approximately linearly through time for a range of parametrizations ( Figure 2E-H), which is in agreement with recent single-cell oocyte measurements in mice (Burgstaller et al, 2018). Previous work has also shown a linear increase in heteroplasmy variance through time for purely genetic models of mtDNA dynamics (see Johnston and Jones (2016)).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…From stochastic simulations we observed that, for sufficiently short times, heteroplasmy variance increases approximately linearly through time for a range of parametrizations ( Figure 2E-H), which is in agreement with recent single-cell oocyte measurements in mice (Burgstaller et al, 2018). Previous work has also shown a linear increase in heteroplasmy variance through time for purely genetic models of mtDNA dynamics (see Johnston and Jones (2016)).…”
Section: Resultssupporting
confidence: 89%
“…In order to fully test our model, further single-cell longitudinal studies are required. For instance, the study by Burgstaller et al (2018) found a linear increase in heteroplasmy variance through time in single oocytes. Our work here has shown that measurement of the network state, as well as turnover and copy number, are required to account for the rate of increase in heteroplasmy variance.…”
Section: Discussionmentioning
confidence: 99%
“…First, the high degree of variability in the mtDNA genotypes of the individual sperm cells is truly fascinating and may explain a great deal about the transmission pattern observed in the paternal line. A similar situation has been previously described in mice, where significant variance in heteroplasmy was recently confirmed at the single-cell level in both oocytes and somatic cells [31]. This genotypic variability appears to be the result of the paternal “mtDNA bottleneck” effect, similar to the well-known maternal mtDNA bottleneck which contributes to the dramatic shifts in mtDNA heteroplasmy that if often observed from mother to offspring.…”
Section: Discussionsupporting
confidence: 76%
“…In the case of this species, the high number of heteroplasmic cells per individual/tissue makes it possible to detect this phenomenon by conventional PCR. However, new techniques such as qPCR (quantitative Polymerase Chain Reaction) and ARMS-qPCR (Amplification Refractory Mutation System-quantitative PCR) are now available to detect very low levels of heteroplasmic cells [7,8]. Electropherogram reads are conditioned by the quality and efficiency of the PCR.…”
Section: Plos Onementioning
confidence: 99%
“…However, this general assumption of uniparentally transmitted, homoplasmic and non-recombining mitochondrial genomes is becoming more and more controversial [3][4][5]. Until now, the presence of different sequences of mtDNA within a cell or individual was a rare phenomenon in animals, but new detection methods based on NGS (Next-Generation Sequencing) or qPCR (quantitative Polymerase Chain Reaction) are allowing their detection [6][7][8][9]. Nowadays, heteroplasmy has been reported in many organisms such as insects [10,11], crustaceans [12,13], molluscs [14], fishes [15,16], frogs [17] birds [18,19], mice [20] and humans [21,22], being the paternal leakage the primary cause of it.…”
Section: Introductionmentioning
confidence: 99%